Pola Eskalasi Konflik Pembangunan Infrastruktur: Studi Kasus Pembangunan Waduk Jatigede Kabupaten Sumedang - Rachmawan, Dicky (UI Scholars Hub, 2015)
This article discusses about the prosess of conflict escalation in Jatigede Dam construction esspecially in pre-construction period from structural and processual point of view using conflict theory. However, height of conflict decreased (deescalation) in empowerment period through community participation and agreement that accomodate community interests. This article emphasizes on the importance of ensuring the rules, policies, and budgets on possibility of problem arising (structural). It is also important to carry out participatory community engagement with bottom-up approach on implementation along with coordination as well as intervention of third party to monitor and to ensure transparent evaluation. This article based on research using qualitative method with porpusive indepth interview